2011
DOI: 10.2106/jbjs.j.00081
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length spp24, but Not Its 18.5-kDa Proteolytic Fragment, Inhibits Bone-Healing in a Rodent Model of Spine Fusion

Abstract: Results from this investigation confirm that the various isoforms of spp24 affect the bone-healing activity of rhBMP-2 in the rat spine fusion model. Thus, proteolytic modification of this protein is a likely mechanism for the regulation of BMP availability in the physiological environment. Future studies will define the roles of these proteins in controlling the activity of BMPs and other members of the transforming growth factor-beta family of cytokines. This information will increase the understanding of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…At the concentrations that we employed, roughly a 30-fold molar excess, Spp24 inhibited the TGF-β2 induced bone formation but Spp14.5 did not. These results are similar to our previously reported findings with respect to BMP-2 in which we demonstrated that full-length Spp24 more strenuously inhibited the activity of BMP than did the smaller forms of Spp24 [16,20]. In general, we propose that Spp24 binds to TGF-β2 and inhibits its activity through a mechanism of extracellular sequestration.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At the concentrations that we employed, roughly a 30-fold molar excess, Spp24 inhibited the TGF-β2 induced bone formation but Spp14.5 did not. These results are similar to our previously reported findings with respect to BMP-2 in which we demonstrated that full-length Spp24 more strenuously inhibited the activity of BMP than did the smaller forms of Spp24 [16,20]. In general, we propose that Spp24 binds to TGF-β2 and inhibits its activity through a mechanism of extracellular sequestration.…”
Section: Discussionsupporting
confidence: 92%
“…TGF-β induced bone formation was inhibited by FL-Spp24, but enhanced by Spp14.5. We also previously reported that FL-Spp24 inhibits BMP-2 and -7-stimulated bone formation, and C-terminal truncation reduces its inhibitory effects [19,20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After sacrifice, the spines were explanted from each animal and subjected to manual assessment as we have previously described (15, 29-31). Gross evaluation and manual assessment results were similar to radiographic findings at 8 weeks.…”
Section: Resultsmentioning
confidence: 99%